2015
DOI: 10.1146/annurev-med-053013-062946
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and Rapid-Acting Antidepressants: A Window into a New Neurobiology for Mood Disorder Therapeutics

Abstract: Ketamine is the prototype for a new generation of glutamate-based antidepressants that rapidly alleviate depression within hours of treatment. Over the past decade, there has been replicated evidence demonstrating the rapid and potent antidepressant effects of ketamine in treatment-resistant depression. Moreover, preclinical and biomarker studies have begun to elucidate the mechanism underlying the rapid antidepressant effects of ketamine, offering a new window into the biology of depression and identifying a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
285
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 350 publications
(302 citation statements)
references
References 110 publications
10
285
1
6
Order By: Relevance
“…2). However, Zanos et al found that both ketamine and (2R,6R)-HNK have no significant effect on mTOR phosphorylation and BDNF levels at 1 h after treatment, which is not consistent with previous studies regarding the involvement of AMPAR-mediated BDNF/TrkB/mTORC1 (mammalian target of rapamycin complex 1) signaling in the rapid antidepressant effects of ketamine [20,21,26] (Fig. 1).…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…2). However, Zanos et al found that both ketamine and (2R,6R)-HNK have no significant effect on mTOR phosphorylation and BDNF levels at 1 h after treatment, which is not consistent with previous studies regarding the involvement of AMPAR-mediated BDNF/TrkB/mTORC1 (mammalian target of rapamycin complex 1) signaling in the rapid antidepressant effects of ketamine [20,21,26] (Fig. 1).…”
contrasting
confidence: 54%
“…Ketamine is widely accepted to act mainly by inhibiting NMDARs in GABAergic interneurons, thus disinhibiting glutamatergic neurons, leading to the activation of downstream signaling and synaptic protein synthesis [20][21][22] (Fig. 1).…”
mentioning
confidence: 99%
“…Although ketamine was generally well tolerated, mild to moderate transient adverse effects were observed during infusion, as perceptual disturbances, dissociation, euphoria, dysphoria, and/or anxiety [46]. Furthermore, physical adverse effects include nausea, dizziness, and minimal increases in blood pressure and heart rate [46].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, physical adverse effects include nausea, dizziness, and minimal increases in blood pressure and heart rate [46]. Thus, pharmacological compounds capable of mimicking the fast antidepressant effects of ketamine but without causing side effects might represent new therapeutic targets in the treatment of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Currently available pharmacotherapies for depression provide some relief for patients, but these agents have significant limitations (1). In this context, new antidepressants with faster onset of action and greater efficacy are needed (2).…”
mentioning
confidence: 99%